Influência das condições de alimentação de glicerol e ornitina na produção de ácido clavulânico por Streptomyces clavuligerus - Teodoro, Juliana Conceição (2008)
The clavulanic acid (CA) is a powerful inhibitor of β-lactamases, enzymes that clives the β- lactam ring of penicillins and cephalosporins, inactivating these compounds. CA is traditionally produced by Streptomyces clavuligerus in batch and fed-batch cultivations. Considering that the products of the catabolism of easily assimilable carbon source repress the biosynthesis of secondary metabolites, including CA, its production in fed-batch mode is preferable because the control of nutrient level can be performed. In the present work the influence of glycerol and ornithine feeding on the clavulanic acid (CA) production by S. clavuligerus in batch and fed-batch cultivations was studied. Batch and fed-batch cultivations were performed at 800 rpm, 0.5 vvm and pH at 6.8. In batch experiments under different concentrations of ornithine, the maximum concentration of CA was within of a closed range between 0.46 and 0.56 g.L-1. Nevertheless, the maximum value of volumetric productivity in CA (Ppmax=13.7 mg.L-1.h-1) was obtained in the experiment with ornithine at concentration of 0.66 g.L-1, a value that is 40% higher than the Ppmax obtained in run control without ornithine. In fed-batch experiments in 5 L bioreactor, with different ornithine feeding conditions, the maximum concentration of CA varied within the limited range of 1.254 and 1.405 g.L-1. Therefore, under these experimental conditions, it can be concluded that the presence of ornithine increases the Ppmax in CA but not its maximum concentration, contradicting literature. The kinetic model considering non-associated production with CA degradation was fitted to the experimental results of the batch and fed-batch cultivations. The experimental results showed that the rate of production of CA and glycerol consumption, were directly related, condition not predicted by model, besides, its negative effect on the AC production after the feeding indicate a possible inhibition/repression effect of glycerol. With the model, it was possible to simulate conditions that the cultivations should be performed with the intention of obtaining larger production of AC. With respect to the influence of glycerol in fed-batch experiments, in the presence of ornithine at the concentration of 3.7 g.L−1 in feeding medium, the maximum CA concentration of 1.506 g.L-1 was obtained in the run BA7 showing a positive effect of the combination ornithine/glycerol in the biosynthesis of CA. In fed-batch experiments in 10-L bioreactor, with different ornithine feeding conditions, the maximum concentrations of CA were near of 1.6 g.L-1, validating the results obtained in 5-L bioreactor.